E0284 Intravascular ultrasound (IVUS) characteristics of premature coronary heart disease (CHD) patients with different risk factors. (17th November 2010) - Lijian, Gao; Jun, Chen; Jilin, Chen; Yuejin, Yang; Shubin, Qiao; Bo, Xu; Jianjun, Li; Xuewen, Qin; Jinqing, Yuan; Yongjian, Wu; Jue, Chen; Shijie, You; et al.
Abstract : Objectives: To observe lesion characteristics of premature coronary heart disease (CHD) patients with different risk factors by intravascular ultrasound (IVUS). Methods: Among 114 premature CHD patients examined by IVUS, quantitative method and qualitative method were adopted to analyse characteristics of coronary artery plaques, and to observe the proportion of different plaques, cross-sectional areas (CSA) surrounded by external elastic membrane, lumen CSA, plaque burden, lumen area stenosis rate and remodelling index of patients with different risk factors. Results: Among the CHD patients with traditional risk factors, there is no statistical difference except in lesion extent and minimum lumen diameter among those CHD patients with hypertension. The lesions are serious and higher ratio of lipid core to plaque among those CHD patients with diabetes. More soft plaques and mixed plaques are observed among those CHD patients with hyperlipidaemia. Lesion length and the ratio of lipid core to plaque were significant difference between premature CHD patients with hyperlipidaemia and control groups. There is no difference on lesion characteristics detected by IVUS between patients with and without family history of CHD. There are more soft plaques and mixed plaques in the premature CHD patients in current smoking group (the p value were <0.05). The lesions were more serious in current smoking patients than those without smoking patients. There were more ruptured plaques in diabetes group. Positive remodelling is a common phenomenon in diabetes group, while more negative remodelling were observed in other groups. Conclusions: The ratio of lipid core to plaque tends to be higher in group with risk factors than that in group without risk factors. More ruptured plaques were observed among those CHD patients with diabetes. Therefore, these risk factors should be strictly controlled in primary prevention of CHD.